Extensões da distribuição de Lindley para análise de dados de sobrevivência - Espirito Santo, Ana Paula Jorge do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Survival Analysis is an area of Statistics that has developed over the last years and many probability distributions have been proposed . In this work, three extensions of Lindley distribution of one parameter obtained by the composition of the distribution process considering the latent structures of activation , minimum and maximum were presented . It is noteworthy that in a context of competing risks or additional risks where it is assumed that the number of causes of failures M follows a Geometric distribution , the distribution obtained by the composition process is a particular case of Marshall-Olkin Extended distribution . The new distributions proposed in this work are: Marshall-Olkin Extended Lindley distribution (Lindley-Geometric distribution), Zero Truncated Lindley-Poisson distribution and Size- Biased Lindley-Poisson distribution. For characterization of distributions some mathematical properties and six estimation methods were presented.

A Análise de Sobrevivência é uma das áreas da Estatística que mais tem se desenvolvido nos últimos anos e muitas distribuições de probabilidade tem sido propostas. Neste trabalho, são apresentadas três extensões da distribuição de Lindley de um parâmetro obtidas pelo processo de composição de distribuição considerando as estruturas latentes de ativação , mínimo e máximo. Vale ressaltar que em um contexto de riscos competitivos ou de riscos complementares, quando assume-se que o número de causas de falhas M segue uma distribuição Geométrica, a distribuição obtida pelo processo de composição é um caso particular da distribuição Extendida Marshall-Olkin. As novas distribuições propostas nesse trabalho são: a distribuição Lindley Extendida Marshall-Olkin (Lindley-Geométrica), a distribuição Lindley-Poisson Truncada no Zero e a distribuição Lindley-Poisson Size-Biased. Para caracterização das distribuições foram apresentadas algumas propriedades matemáticas e seis métodos de estimação.
Keywords: Computação - Matematica; Análise de sobrevivência (Biometria); Riscos competitivos; Sistemas de parâmetros distribuídos; Estatistica - Processamento de dados; Computer science - Mathematics